PSCAR: a proactive-optimal-path selection with coordinator agents assisted routing for vehicular ad hoc networks. (2018) - Boussoufa-Lahlah, Souaad; Semchedine, Fouzi; Bouallouche-Medjkoune, Louiza; Farhi, Nadir
In this paper, we propose the proactive-optimal-path selection with coordinator agents assisted routing (PSCAR) protocol for VANETs. The main idea of PSCAR is to contribute static nodes as coordinator agents placed at each intersection. Since the coordinator agents are static nodes, each one knows all the paths to any other coordinator agent in the network. Thus, instead of searching an optimal path toward the destination, PSCAR will determine an optimal path to the nearest coordinator agent to the destination so as to better anticipate any change of the destination's position. The optimal path is selected according to two criteria: the total physical distance and the vehicle density on the path. To evaluate the performance of PSCAR, we used the Network Simulator 2 (ns-2) and the mobility simulator SUMO. We compare our scheme with some existing solutions at the aim of showing its effectiveness, in terms of packet delivery ratio, end-to-end delay, and network overhead.